Coping Strategies in Health Professionals Facing Covid-19 - Dullius, Willian Roger (2021)
In view of the importance of developing protective actions to mental health in pandemic contexts, this study aimed to gather evidence about coping mechanisms that health professionals use during the  COVID-19 pandemic. This systematic review, developed from international and Brazilian databases between November/2019 and July/2020, identified 3821 potentially relevant articles, published in English and Portuguese. Checking the appropriateness of the articles to the objective of the review resulted in the selection of 23 articles that were read in full, eight of which were selected for this review. The main coping mechanisms described were psychological support from relatives, colleagues, institutions, and patients; availability of continuing education and PPE; spirituality; time for hobbies. Promoting effective and sustainable coping strategies is vital to enable the health professionals to feel capable of facing one of the major contemporary humanitarian challenges - COVID-19 pandemic.